The Hidden Facets: Uncovering the Influence of Region on Social Housing Unit Distribution in Brazil - Frederico G. P. Moreira; Lucas E. C. Silva; Victor I. M. dos Santos (Buildings, 2023)
The Brazilian housing program, Minha Casa, Minha Vida (MCMV) (My House, My Life), was launched in 2009 to address the housing deficit issue, with the goal of distributing contracted housing units throughout the Brazilian territory. However, the program faces criticisms regarding the distribution of these units. Thus, this paper aims to analyze the distribution heterogeneity of these contracted housing units (CHUs). Two analytical approaches were employed: temporal and spatial (states). To achieve this objective, inferential methods such as Ordinary Least Squares (OLS), Spatial Autoregressive Model (SAR), and panel data regressions were employed. The findings indicate that, from a temporal perspective, there is a positive relationship between the urban housing deficit (UHD) and CHUs. However, the relationship is negative from a spatial perspective, characterizing such heterogeneity among the states. In addition, bordering regions are subject to mutual spatial influences in terms of contracted units, thereby reinforcing this heterogeneity over time.